1999
DOI: 10.1523/jneurosci.19-17-07468.1999
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Expression of a Queen Pheromone-Binding Protein in the Honeybee: an Olfactory-Specific, Developmentally Regulated Protein

Abstract: Odorant-binding proteins (OBPs) are small abundant extracellular proteins thought to participate in perireceptor events of odor-pheromone detection by carrying, deactivating, and/or selecting odor stimuli. The honeybee queen pheromone is known to play a crucial role in colony organization, in addition to drone sex attraction. We identified, for the first time in a social insect, a binding protein called antennal-specific protein 1 (ASP1), which binds at least one of the major queen pheromone components. ASP1 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
89
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(90 citation statements)
references
References 49 publications
1
89
0
Order By: Relevance
“…Between 2 and 3 M PBP there is a sharp increase in pheromone binding affinity (12), which possibly reflects a micromolar dissociation constant for the PBP dimer. In several studies, dimeric PBP was observed directly in native electrophoretic gels (12,40) or by gel filtration chromatography (39,41,42). Interestingly, the monomer-dimer equilibrium shifts toward the monomer below pH 5.5 (40).…”
Section: Discussionmentioning
confidence: 99%
“…Between 2 and 3 M PBP there is a sharp increase in pheromone binding affinity (12), which possibly reflects a micromolar dissociation constant for the PBP dimer. In several studies, dimeric PBP was observed directly in native electrophoretic gels (12,40) or by gel filtration chromatography (39,41,42). Interestingly, the monomer-dimer equilibrium shifts toward the monomer below pH 5.5 (40).…”
Section: Discussionmentioning
confidence: 99%
“…Although a few studies have sought to implicate various small soluble proteins in pheromone recognition (17,(20)(21)(22)(23), it seems more likely that these proteins are involved in generic odorant solubilization and play little role in odor coding (24,25). The only known hymenopteran pheromone ligand-receptor pair to date is the honey bee (Apis mellifera) queen pheromone 9-ODA and the OR AmelOR11 (26).…”
Section: Significancementioning
confidence: 99%
“…3). The ABPX subfamily also includes three beetle OBPs, the queen pheromone-binding protein from the honey bee Apis mellifera, and an OBP from the "true bug" Lygus lineolaris (Wojtasek et al 1998(Wojtasek et al , 1999Danty et al 1999;Vogt et al 1999). We have named another OBP subfamily the CRLBP family (Fig.…”
Section: Drosophila Obps Within the Insect Obp Familymentioning
confidence: 99%
“…The five CRLBP OBPs share an average of 22% identity. The CRLBP subfamily is polyphyletic and includes two Drosophila Obps (Obp19d and Obp28a) along with OBPs from the beetle Phyllopertha diversa (P. div OBP2) and the honey bee A. mellifera (A. mel ASP2; Danty et al 1999;Wojtasek et al 1999). The sand fly Lutzomyia longipalpis salivary protein SL1 (Charlab et al 1999) clusters with a group of Drosophila OBPs, including most of those encoded by the 14 Obp genes in cytological region 56E-57A.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation